Adaptive Structuration and Post-COVID-19 Drivers of Cross-Border Consumer Purchase Intention: A PLS-SEM Study at Birgunj, Nepal - Das, Saraswati; Paudel, Udaya Raj (International Research Journal of MMC, 2025)
Cross broader business is a significant contributor to regional trade, but the consumers incur some problems like transportation inefficiency and difference in prices. The purpose of the study is to explore the influence on cross-border purchase intention of customers in business at Birgunj-border at Nepal especially after the COVID-19. The philosophy of research adopted was explanatory research design that was used to address the relationship between cross-border motivations and purchase intention. The research used the Adaptive Structuration Theory because of the conceptual model developed by Han and Kim. Research was conducted on 403 consumers, who bought items at Birgunj-border through convenient sampling and KOBO Toolbox. Both descriptive statistics and inferential ones were utilized, and PLS-SEM was applied to determine how hedonic, social, and utilitarian motivations affect the purchase intention. Protectionism is a prevalent issue beyond borders because cross-border shoppers face numerous difficulties in transportation management and affordable prices, and these difficulties can be solved by enhancing the activities of governments and business enterprises. The hedonistic and social cross-border motivation were identified as having a significant purchase intention, whereas utilitarian motivation did not indicate a significant effect. The research notes that consumer pleasure and social life are major stimulas of cross-border shoppers and to facilitate efficiency in trade, infrastructure and management should be improved. The policymakers and business operators must concentrate addressing the areas of streamlined transportation, setting fair prices, attracting cross border consumer activity to enhance trade flows and contribute to the economy.